Morphological and Molecular studies of Acanthobra marmid Heckel, 1843 (Piscies, Cypriniformes, Leuciscidae) from the Middle of Iraq - Dyia Hadi, Hind; Hassan Baraaj, Abed; Hussein Ali, Atheer (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
Leuciscidae species are the abundant and widely distributed fish species in Iraq's inland waters. They are complex species, and morphology makes them difficult to identify. Molecular analysis achieved and confirmed the morphological characters. Twenty specimens of Acanthobrama marmid were collected from two localities at Tigris River, in the middle of Iraq; 15 specimens from the Al-Zubaydia sub-district and five specimens from Al-Tharthar Lake. We used the mitochondrial DNA cytochrome b (cytb) gene to sequence the DNA of A. marmid. The following analysis are compared the sequences with those of other fish genera and species found in the Gene Bank. The barcoding result (DNA sequencing) in fishes found in the same family  (Leuciscidae) showed that it fit with A. marmid. We conclude, the results of the current study, by using the cytochrome b (cytb) gene, are a successful tool and confirmed the morphological characters for accurate identification of A. marmid.